Institutional Experiments and Documentary Initiatives in the Umbrian Communes of ‘Popolo’ from the Half of the Thirteenth Century (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
The aim of this research is to identify the initiatives clearly promoted by the populus in the field of production and documentationmanagement. Umbria is chosen as a field of study because of its historical and geographical context, characterized by high density of small and medium city-states and by a remarkably rich municipal documentation. In this area municipal records directly related to the populus’ institutional bodies have been identified and analysed. The gradual affirmation of the populus in the Umbrian city-states government aswell asmany documentary initiatives specifically commissioned by popular magistrates are characterized by the extreme variety of the solutions adopted both in the institutional field and in the documentation management. The re-writing of certain acts operated by the officium capitanei populi, seems to indicate a direct interference and a control of the capitaneus in performing certain tasks by other municipal officiales.DOI 10.17464/9788867742707
Keywords: Umbrian city-states; municipal documentation; 13th century; popular party